Foreign Ownership and Corporate Financial Decision Making: A Review and Future Research Agenda - Kitri, Mandra Lazuardi; Wiryono, Sudarso Kaderi; Nainggolan, Yunieta Anny (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2022)
Individuals, firms, and even countries face scarcity due to limited resources. To overcome this problem, especially in the need for capital resources, firms and countries try to acquire additional capital externally through foreign investment. Previous research has been conducted to examine the effect of foreign ownership on a firm’s decision-making and performance. However, the systematic literature review shows that the results are still inconclusive and bring confusion for firms and governments in determining their strategy for promoting foreign investment. There are two gaps identified surrounding current research on foreign ownership that needs special attention. First, most research considers foreign ownership as an ownership type and puts less attention on the actual ownership types. Second, research has found that different characteristics of the home or host country involved in foreign investment may moderate the relationship between foreign ownership and a firm’s decision-making but only considers a one-sided observation of country characteristics (home or host country only). This research proposes future research agenda in examining how different foreign owner’s ownership types affect a firm’s decision-making, risk, and performance and whether country characteristics differences moderate the relationships between foreign owner’s ownership types, firm’s decision-making, risk, and performance. Individu, perusahaan, dan bahkan negara menghadapi persoalan kelangkaan akibat terbatasnya sumber daya. Untuk menghadapi hal tersebut, terutama terkait dengan kebutuhan modal, perusahaan dan negara berupaya untuk memperoleh tambahan modal melalui sumber eksternal berupa investasi asing. Penelitian terdahulu telah dilakukan untuk mengetahui efek dari kepemilikan asing terhadap pengambilan keputusan dan kinerja perusahaan. Namun, hasil penelitian-penelitian tersebut masih beragam dan membawa kebingungan bagi perusahaan dan negara dalam memutuskan strategi untuk mempromosikan investasi asing. Terdapat dua persoalan yang ditemukan dalam penelitian-penelitian terkait kepemilikan asing. Pertama, sebagian besar penelitian menilai kepemilikan asing sebagai jenis kepemilikan dan kurang memperhatikan jenis pemilik asing sesungguhnya. Kedua, beberapa penelitian menemukan bahwa karakteristik negara memoderasi hubungan antara kepemilikan asing dan pengambilan keputusan serta kinerja perusahaan, namun penelitian-penelitian tersebut hanya mempertimbangkan satu sisi karakteristik negara (asal investor atau lokasi perusahaan). Penelitian ini mengusulkan agar agenda riset masa depan dapat menggali pengaruh perbedaan tipe kepemilikan pemilik asing terhadap pengambilan keputusan, risiko, dan kinerja perusahaan serta bagaimana perbedaan karakteristik negara dapat memoderasi hubungan antara tipe pemilik asing dengan pengambilan keputusan, risiko, dan kinerja perusahaan.